Pemanfaatan Bacillus thuringiensis dan Kompos Trichoderma sp. untuk Mengendalikan Hama dan Penyakit Utama Tanaman Kubis (Brassica oleraceae L.) di Desa Bangli, Kecamatan Baturiti, Kabupaten Tabanan - I KETUT PURNA YASA; GUSTI NGURAH ALIT SUSANTA WIRYA; MADE SUPARTHA UTAMA; I PUTU SUDIARTA (Program Studi Agroekoteknologi, Fakultas Pertanian, Universitas Udayana, 2020)
The utilization of Bacillus thuringiensis and Compost Plus Trichoderma sp to Control the Key Pests and Diseases of Cabbage (Brassica oleraceae) in Bangli Village Baturiti District, Tabanan Regency. The experimental design was used Factorial Randomize Complete Blok Design, with two factors: Factor I : (A) Seedling of Trichoderma sp., Soil containing compost and Trichoderma sp., (B) Seedling of Trichoderma sp., Soil containing compost but without Trichoderma sp., (C) Cow manure and spice extracts bali. Factor II : (a) B. thuringiensis and (b) Without B. thuringiensis. The results treatment of seedling with Trichoderma sp., Soil containing compost and Trichoderma sp. showed the lowest percentage of the disease (32.5%), and disease severity (19.37%) if compare with other treatments. On the order hand B. thuringiensis was effect to the population of C. binotalis and total of cabbage production. The population of C. binotalis was lower on cabbage with BT treatment (2,33) if compare without BT treatment (9,65 ). Treatment of seedling with Trichoderma sp., Soil containing compost and Trichoderma sp. showed the highest total yield (16 kg/plot), as well as the treatment of B. thuringiensis was highest total of yield (16.20 kg/plot).